Feiyanning Formula Induces Apoptosis of Lung Adenocarcinoma Cells by Activating the Mitochondrial Pathway - Zhu, Li-Min; Shi, Hai-Xia; Sugimoto, Masahiro; Bandow, Kenjiro; Sakagami, Hiroshi; Amano, Shigeru; Deng, Hai-Bin; Ye, Qing-Yu; Gai, Yun; Xin, Xiao-Li; Xu, Zhen-Ye (Frontiers in Oncology, 2021)
Feiyanning formula (FYN) is a Traditional Chinese Medicine (TCM) compound used for more than 20 years in the treatment of lung cancer. FYN is composed of Radix Astragali, Rhizoma Polygonati, Rhizoma Atractylodis Macrocephalae, Cornus officinalis, polyphylla and beehive, all of them have been proved to have anti-tumor effect. In this study, we used the TCM network pharmacological analysis method to perform compound collection, disease target collection, compound target prediction, biological signal and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis. It was predicted that the activation of mitochondrial pathway might be the molecular mechanism of the anti-lung cancer effect of FYN. The results of in vitro experiments showed that FYN had inhibitory effect on the growth of lung cancer cells in a dose-dependent and time-dependent manner. Moreover, FYN induced G2/M cell cycle arrest and apoptotic cell death as early as 6 hours after treatment. In addition, FYN significantly induced mitochondrial membrane depolarization and increased calreticulin expression. Metabonomics analysis showed the increase of ATP utilization (assessed by a significant increase of the AMP/ATP and ADP/ATP ratio, necessary for apoptosis induction), and decrease of polyamines (that reflects growth potential). Taken together, our study suggested that FYN induced apoptosis of lung adenocarcinoma cells by promoting energy metabolism and changing mitochondrial membrane potential.